Access to justice, easy-to-read sentences for girls, boys, adolescents and people with disabilities (Brasilia Rules) - Chípuli Castillo, Arturo Miguel (2023)
Children, adolescents and persons with disabilities constitute a particularly vulnerable social group in our society; their families face daily obstacles that restrict and limit the full exercise of their human rights; as well as their inclusion in society and the human right of access to justice. In order to guarantee access to justice for the aforementioned sector, the judiciaries in various countries, including Mexico, Peru, Argentina and Spain, have established a jurisdictional policy seeking to draft some sentences in a format that is easy for the courts to read. and the heads of the administration of justice in matters involving children and people with disabilities. The foregoing, based on various international instruments, such as: articles 8 and 25 of the American Convention on Human Rights (ACHR), articles 2, 13 and 21 Convention on the Rights of Persons with Disabilities; Rules 58, 59, 60, 77 and 78 of the Brasilia Rules, among others. Consequently, in this article, the work that has been carried out by the judiciary in the aforementioned countries with the primary purpose of protecting and guaranteeing the human right of access to justice for children and adolescents will be analyzed as a synthesis. people with disabilities, in compliance with its internal regulations and international instruments.